IMPLEMENTASI SISTEM OTENTIKASI PADA PENGGUNA JARINGAN HOTSPOT DI UNIVERSITAS KANJURUHAN MALANG GUNA MENINGKATKAN KEAMANAN JARINGAN KOMPUTER - Ardian, Yusriel (Jurnal Informatika, 2012)
The number of client server applications using both desktop and WEB Application makes every user must have a lot of user id and password that must be memorized, because each application must require authentication in order to utilize the application for security reasons. Besides the development of network media is also growing use of both wired and wireless. From the above explanation RADIUS technology is desperately needed in the case described above, since the RADIUS method allows a user simply has a userID for access to multiple applications, both desktop and WEB application. RADIUS can also integrated method of wired and wireless media.